James and Carnap on philosophical systems and the role of temperaments. (21st January 2023) - Simpson, Shawn
Abstract: The relationship between American pragmatism and logical empiricism is complicated at best. The received view is that by around the late 1930s or early 1940s pragmatism had been replaced, supplanted, or eclipsed by the younger and more logic‐oriented form of empiricism developed in interwar Vienna. Recently, however, this picture has been challenged, and this paper offers further reasons for thinking that the received view is inadequate. Through a critical examination of William James's Pragmatism and "The Sentiment of Rationality" and Rudolf Carnap's "Elimination of Metaphysics Through Logical Analysis of Language" and other works, the paper builds a case for the existence of a rather striking correspondence between the work of one of pragmatism's most vaunted figures and the thought of logical empiricism's most famous advocate. Not only were both philosophers interested in what might be called metaphilosophy or the psychology of philosophy, both held very similar deflationary views.